2016
DOI: 10.1016/s2214-109x(16)30148-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and antimicrobial resistance of sepsis pathogens in neonates born in tertiary care centres in Delhi, India: a cohort study

Abstract: Indian Council of Medical Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
118
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(160 citation statements)
references
References 35 publications
(50 reference statements)
17
118
6
Order By: Relevance
“…The prevalence of neonatal sepsis due to MDR strains in our study was 73.91%. MDR among gram-negatives and gram-positives was 80.76 and 52.94% respectively in our study, which is in agreement with the findings of DeNIS Collaboration from India and Labi AK et al from Ghana [13,6].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The prevalence of neonatal sepsis due to MDR strains in our study was 73.91%. MDR among gram-negatives and gram-positives was 80.76 and 52.94% respectively in our study, which is in agreement with the findings of DeNIS Collaboration from India and Labi AK et al from Ghana [13,6].…”
Section: Discussionsupporting
confidence: 93%
“…The majority of the isolates were gram-negative, similar to the findings of Shrestha S et al and that of investigators of the Delhi Neonatal Infection Study (DeNIS) Collaboration [11,13]. In contrast, Peterside O et al in Nigeria and Sharma P et al in India showed a preponderance of gram-positive organisms of which Staphylococcus aureus was the most prevalent [14].…”
Section: Discussionsupporting
confidence: 81%
“…In previous studies done in India, it has ranged from 16% to 54%. [ 3 4 5 6 7 8 ] The culture positivity might be an underestimation of actual status in our study, as anaerobic organisms were not tested in our institution. Outborn babies were excluded from our study due to difficulties in obtaining accurate antenatal and perinatal data.…”
Section: Discussionmentioning
confidence: 83%
“…Even studies from Egypt addressing this problem studied multi drug resistance either collectively [18] or in relation to late onset sepsis only [19]. The worrisome rise in levels of antimicrobial resistance among pathogens retrieved from NICUs highlight the needs for better understanding of the problem of early onset sepsis and implementing strategies to combat, especially in countries with limited resources [20]. …”
Section: Discussionmentioning
confidence: 99%